What have the changes made to primary and secondary assessment frameworks since 2014 done to the 'London effect' in school performance? (UCL Press, 2018)
This article examines whether the so-called 'London effect', in which London's schools improved rapidly and outperformed the rest of England on key performance measures between 2003 and 2013, has persisted through the high levels of change that have continued to characterize the school system in England since 2013. Using detailed analysis of educational attainment data, its primary focus is on determining whether the introduction in 2014 of significant changes to the primary curriculum and the national assessment frameworks in both primary and secondary phases affected the performance of London's schools in 2016, when the first examinations were taken under the new assessment systems.